Blockchain technology and the role of blockchain in uzbekistan - Boburjon Tojimurodovich Xidirov; Mooniddinov Abduvohid Muhiddin o'g'li (Zien Journals, 2022)
This article gives you a brief overview on blockchain technology and its benefits. There is talk about the development of blockchain in Uzbekistan and in what areas the blockchain can be widely used.
Keywords: Digital economy; blockchain; bitcoin; transaction